The e-Library of the National Library of Sakha Republic (Yakutia): The general approaches - S. Maksimova V.; С. Максимова В. (Scientific and Technical Libraries, 2021)
The upgrade project for the Electronic Library of the National Library of the Republic of Sakha (Yakutia) is discussed. The goal is to provide remote access to its digital content, to expand and develop library information services in the digital environment. The e-library enables to improve library services of the republican population and to raise the profile of the library in the modern technological world. The elibrary’s new services emerge at the synthesis of new information technologies (implementation tool) and new approaches to traditional library and bibliographic processes. The user-group oriented segments were designed ("School", "Reading since very birth", "Science in Yakutia", "Electronic publishing house") which enables to meet information demands to the fullest extent possible. The options for using personal accounts, statistical performance indicators, e-library document collection, resources selection and systematization, and grouping methods are characterized in brief. The search instrument makes an important performance indicator; it can be used for every segment and collection and is locked to descriptive metadata fields for all types of resources (formats). The concept of creating Single Library and Information Environment based on the National Library of the Republic of Sakha (Yakutia) provides the organizational and technological prospects for the e-Library. Рассмотрен проект по модернизации информационной системы «Электронная библиотека Национальной библиотеки РС (Я)», цели которой – обеспечение удалённого доступа к электронному контенту, расширение и развитие информационных услуг библиотеки в электронной среде. В данном случае электронная библиотека – это способ усовершенствовать библиотечное обслуживание населения республики и повысить статус библиотеки в современном технологическом мире. Представлены новые сервисы (услуги) электронной библиотеки как результат синтеза информационных технологий (инструмент реализации) и свежего взгляда на традиционные библиотечнобиблиографические процессы. Разработаны сегменты для разных категорий пользователей («Школа», «Читаем с рождения», «Наука Якутии», «Электронное издательство»), что позволяет наиболее полно удовлетворять информационные потребности каждой отдельно взятой группы читателей. Кратко охарактеризованы: варианты использования личного кабинета и основные статистические показатели работы; документный фонд ЭБ, отбор и организация ресурсов, методы группировки. Отмечено, что поисковый инструмент – важный показатель функциональности электронной библиотеки: он работает по всем сегментам и подборкам; ведётся по полям описательных метаданных для всех типов ресурсов (форм представления). Показаны поисковые возможности электронной библиотеки. Организационно-технологическое перспективы формирования представлены концепцией создания единой библиотечно-информационной среды на базе Национальной библиотеки Республики.